Locus of Control as a Moderator of the Effects of Organizational Commitment and Pay-for-Performance on Performance of Tax Officers - Bandang, Agus; Usman, Asri; Bela, Made Gde Satria (Information Management and Business Review, 2017)
This study aims to determine the effect of organizational commitment and pay-for-performance on performance of tax officers with locus of control as moderating variable. This research is a quantitative descriptive study. Data on this research was obtained through questionaires. Population of this study consists of 104 tax officer of South Makassar Small Taxpayers Office of which is randomly chosen 83 tax officers as a sample to answer research questionnaires. Analysis of this study is using regression analysis with residual analysis method to test the effect of moderating variable. The results of this research indicate that (1) organizational commitment has a positive effect on performance of tax officers, (2) locus of control is able to moderate the effect of organizational commitment on performance of tax officers, (3) pay-for-performance has a positive effect on performance of tax officers, and (4)) locus of control is able to moderate the effect of pay-for-performance on performance of tax officers.